Microstructure examination of illiquid contracts : evidence from the Singapore derivatives market. - Kho, James Chung Wah. (2008)
This study investigates the nature of intraday and daily trading activity, volatility of return and bid-ask spread for three illiquid contracts traded on the Singapore International Monetary Exchange (SIMEX) Limited from February 1995 to September 1999.